Metode Fuzzy untuk Mengidentifikasi Kepribadian Siswa - Nanda Putra; Ilham Danu Saputra (Jurnal Sistim Informasi dan Teknologi, 2022)
Personality identification is one of the important things to know yourself and others. This identification is done based on the personality traits possessed by a person based on Kant's personality theory. Not a few teachers who do not understand the student's personality, in the teaching and learning process some teachers who do not understand the student's personality, a teacher will find it difficult to convey learning materials that will attract students' interest which has an impact on the knowledge transfer process being hampered. Then the Fuzzy Tsukamoto method is used to identify the student's personality. The purpose of this research is to help teachers in classifying and recognizing students' personalities so that it is easier to determine treatment in developing their talents and interests. The system input is obtained from personality traits that are suitable for students. The knowledge base was obtained from a Child Clinical Psychologist and was built with the qadidah (IF-THEN). The output of the Fuzzy calculation is that students have a Sanguine, Choleric, Melancholic or Phlegmatic personality. The results of testing this method by doing calculations and testing the system, it is obtained that personality outputs are in accordance with the personality characteristics of students and are running well. So it can be recommended to help teachers in determining the treatment of students.